Possible involvement of A1 receptors in the inhibition of gonadotropin secretion induced by adenosine in rat hemipituitaries in vitro - DINIZ, Domingos Luiz Wanderley Picanço (2012)
We investigated the participation of A1 or A2 receptors in the gonadotrope and their role in the regulation of LH and FSH secretion in adult rat hemipituitary preparations, using adenosine analogues. A dose-dependent inhibition of LH and FSH secretion was observed after the administration of graded doses of the R-isomer of phenylisopropyladenosine (R-PIA; 1 nM, 10 nM, 100 nM, 1 µM and 10 µM). The effect of R-PIA (10 nM) was blocked by the addition of 8-cyclopentyltheophylline (CPT), a selective A1 adenosine receptor antagonist, at the dose of 1 µM. The addition of an A2 receptor-specific agonist, 5-N-methylcarboxamidoadenosine (MECA), at the doses of 1 nM to 1 µM had no significant effect on LH or FSH secretion, suggesting the absence of this receptor subtype in the gonadotrope. However, a sharp inhibition of the basal secretion of these gonadotropins was observed after the administration of 10 µM MECA. This effect mimicked the inhibition induced by R-PIA, supporting the hypothesis of the presence of A1 receptors in the gonadotrope. R-PIA (1 nM to 1 µM) also inhibited the secretion of LH and FSH induced by phospholipase C (0.5 IU/ml) in a dose-dependent manner. These results suggest the presence of A1 receptors and the absence of A2 receptors in the gonadotrope. It is possible that the inhibition of LH and FSH secretion resulting from the activation of A1 receptors may have occurred independently of the increase in membrane phosphoinositide synthesis.